UNDANG-UNDANG NOMOR 8 TAHUN 2012 DALAM KAITANNYA DENGAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 52/PUU-X/2012. - Mursyid, Husni A. Jalil, Iskandar A.Gani (Jurnal Ilmu Hukum, 2015)
Abstract: Indonesian political system is a multi-party system, aiming is to adopt the national interests of heterogeneous nature. The legal basis of political parties is the Law Number 2, 2011 on Political Parties and the Law Number 8, 2012 on the Implementation of legislative elections. However, the existence of the Law Number 8, 2012 can be seen by the Constitutional Court Decision No. 52 / PUU-X / 2012, the point is to simplify the political parties contesting the election. Changes in the system are highlighted in the decision of the Court that is the application of Parlimentary Threshold, which previously was the electoral threshold. As a result, the Court's decision is not his next political party that does not cover the seats in parliament in the last election, to be able to follow the 2014 election; hence it discriminates against the value of democracy in Indonesia. Normative juridical is aplled in this research by applying historical approach. This is prescriptive analytical research. Secondary data including primary, secondary and tertiary legal materials. The data are then classified, and grouped, these will be analyzed with a qualitative approach. Keywords : Political Parties, Political Party Simplification. Abstrak: Sistem politik dianut Negara Indonesia adalah sistem multi partai, tujuannya adalah mengadopsi kepentingan warga negara yang sifatnya heterogen. Dasar hukum dari partai politik yaitu UU No. 2 Tahun 2011 tentang Partai Politik dan UU No. 8 Tahun 2012 tentang Penyelenggaraan Pemilu Legislatif. Namun, keberadaan dari UU No. 8 Tahun 2012 telah diputuskan oleh MK dengan Putusan No. 52/PUU-X/2012, yang intinya adalah menyederhanakan partai politik peserta pemilu. Perubahan sistem yang ditekankan dalam putusan MK tersebut adalah penerapan Parlimentary Treshold, dimana sebelumnya adalah electoral threshold. Akibat dari putusan MK tersebut adalah tidak bisa ikutnya partai politik yang tidak mencakupi kursi di parlemen pada pemilu sebelumnya, untuk dapat mengikuti pemilu 2014. Sehingga hal tersebut mendiskriminasi nilai demokrasi di Indonesia. Adapun metode penelitian yang digunakan yaitu penelitian yuridis normative, dengan pendekatan historical approach. Spesifikasi penelitian adalah preskriptif analitis. Adapun sumber data penelitian ini digunakan data sekunder yang mencakupi bahan hokum primer, bahan hokum sekunder dan bahan hokum tersier. Setelah data dikumpulkan, diklasifikasi, dan dikelompokkan maka akan dianalisis dengan pendekatan kualitatif. Kata kunci : Partai Politik dan Penyederhanaan Partai Politik.